Algorithmic Interaction in Public Administration: Data-Based Communication and Political Participation in Public Institutions - Tutar, Hasan (Public Governance, Administration and Finances Law Review, 2025)
This study investigates the influence of algorithmic interaction on public relations and political participation within public institutions. Digitalisation transforms traditional forms of communication, emphasising data-driven, transparent and accountable structures. The study uses OECD, Eurostat and World Bank data to create a balanced panel dataset for the EU27 countries from 2015 to 2024. Panel regression, causality tests, cointegration analyses and dynamic panel methods were applied. The findings suggest that social media use enhances e-government participation and that these interactions strengthen digital democracy. Furthermore, renewable energy and energy dependency have indirect relationships with digitalisation. The study justifies and stress-tests a proxy for algorithmic content density, documenting dynamic effects using System GMM with transparent instrument reporting. Subsample and interaction analyses reveal heterogeneous returns for OMS versus NMS. Policy recommendations emphasise algorithmic transparency, inclusive access and ethics by design.